(untitled) (Research, Society and Development, 2022)
Objective: to analyze alcohol consumption, physical activity level (PAL) and body composition (WC) in recreational walking practitioners. Methods: 125 women and 148 men participated in the study, with a mean age of 37.4 ± 12.8 and 40.0 ± 13.8 years, respectively. The profile of alcohol consumption was evaluated by the Alcohol Use Disorder Identification Test, the NAF by the International Physical Activity Questionnaire-Short Form (IPAQ-SF), for WC, body mass (BM), height was collected, and the height was calculated. body mass index (BMI), and waist circumference (WC) was measured. Descriptive and inferential statistics were applied, adopting p<0.05. Results: An association was found (p = 0.04), men are 3.16 times more likely to be at risk for consumption than women. 82.4% of women and 72.3% of men classified themselves as physically active. AC was associated (p = 0.02), women had a metabolic risk 1.75 times higher. When compared by age groups, middle-aged women had higher BM (p = 0.02), BMI (p < 0.001) and WC (p < 0.0001) than younger women. Middle-aged (p = 0.0002) and elderly (p = 0.002) men were identified with a higher AC than young men. Conclusion: Young men at high risk for alcohol consumption. In general, the population was defined as being at low risk for alcohol consumption and physically active. Although the population of the population has not been identified as having an undesirable WC, the results reinforce that PA can be used as a strategy for healthy habits.